Scramsis Game (Syntak Scramble) Innovation Of Basic Programming Educational Games For Students Of Class X Tkj Smk Muhammadiyah 1 Wates - Ahmad Muzaki Salman Alfaris (Institute of Computer Science (IOCS), 2021)
This study aims to: develop a Scramsis game that contains basic programming material for class X TKJ SMK Muhammadiyah 1 Wates and test the quality of the Scramsis game based on the ISO 25010 quality standard. This research is a research and development research using the Waterfall model which includes communication, planning, modeling, construction, and distribution. The functional suitability quality test was carried out by 2 developers, while the usability test was carried out by students of class X TKJ SMK Muhammadiyah 1 Wates. The results of this study are: (1) Game Scramsis has six main menus, namely let's play, how to play, settings, profiles, instructions, and exit. Scramsis has 3 different levels of difficulty.. Game Scramsis got a score of 100% on the functional suitability quality test which means very high quality, 100% on the compatibility quality test which means very high quality. Scramsis' performance efficiency test is seen from CPU and memory usage, the average CPU usage of Scramsis is 2.71%, when compared to the CPU limit set by little eye, which is 15%, this usage is still very safe. Scramsis' performance efficiency test is seen from CPU and memory usage, the average CPU usage of Scramsis is 2.71%, when compared to the CPU limit set by little eye, which is 15%, this usage is still very safe. The use of scramsis memory is 129 MB and does not experience force close. The usability test was carried out on class X TKJ. Scramsis' performance efficiency test is seen from CPU and memory usage, the average CPU usage of Scramsis is 2.71%, when compared to the CPU limit set by little eye, which is 15%, this usage is still very safe. The use of scramsis memory is 129 MB and does not experience force close. The usability test was carried out on class X TKJ SMK Muhammadiyah 1 Wates and got a score of 80.02% which was included in the quality category and the Cronbach alpha reliability value from the usability test questionnaire was 0.828 which means good.